Effects of Shenfu Injection in the Treatment of Septic Shock Patients: A Multicenter, Controlled, Randomized, Open-Label Trial. (30th June 2016) - Li, Yi; Zhang, Xinchao; Lin, Peihong; Qiu, Haibo; Wei, Jie; Cao, Yu; Pan, Shuming; Walline, Joseph; Qian, Chuanyun; Shan, Zhigang; Yu, XueZhong
Abstract : The effect of Shenfu on biochemical parameters and survival during resuscitation in patients with septic shock was examined. This was a multicenter, controlled, randomized, open-label trial carried out in 210 patients with septic shock from seven medical centers in China. They were randomized to Shenfu or saline. The primary outcome was lactate clearance. The secondary outcomes were shock index normalization, dose of vasopressors, ICU stay, hospital stay, and mortality. A total of 199 patients completed the trial. Blood pressure, heart rate, and other routine lab tests showed no difference between the groups. Lactate levels and lactate clearance were similar between the two groups. Hospital and ICU stay were similar between the two groups. When considering all patients, the 7- and 28-day mortality were similar between the two groups, but when considering only patients with lactate levels ≥4.5 mmol/L, the Shenfu group showed a better 7-day survival than the control group (7 days: 83.3% versus 54.5%, P = 0.034 ; 28 days: 72.7% versus 47.6%, P = 0.092 ). Shenfu may improve the 7-day survival in patients with impaired lactate clearance (≥4.5 mmol/L), but the mechanism for this effect is unclear. Additional studies are necessary to characterize the hemodynamic changes after Shenfu infusion. This trial is registered withChiCTR-TRC-11001369 .